Case report: An EEG captured case of migralepsy/migraine aura-triggered seizures - Hareem, Anam; Pahlavanzadeh, Mahsa; Calvo, Nicholas E.; Monjazeb, Sanaz; Anyanwu, Chinekwu (Frontiers in Neurology, 2022)
Introduction Migraine and epilepsy are common chronic neurological disorders presenting with paroxysmal attacks of transient cerebral dysfunction, followed by subsequent return to baseline between episodes. The term “migralepsy” has been proposed to define migraine-triggered epileptic seizures classified by the ICHD-III as a complication of migraine with an aura. Case A 55-year-old man with a 30-year history of migraine without aura presented with a new onset left parietal pain accompanied by visual disturbances occurring up to 20 times per day. His visual distortions included kaleidoscopic vision, flashes of shadows, and a right superior quadrantanopia lasting 20 min. He described discrete 2-min episodes of scintillating scotomas in his right visual field. Ictal EEG demonstrated a left occipital onset focal aware seizure with his clinical symptoms. The patient was started on valproic Acid and has remained asymptomatic. Discussion The diagnostic criteria as set out by the ICHD-III for migralepsy and other syndromes with migrainous and ictal features remain confusing for practitioners as there is much overlap in clinical manifestations of these entities. EEG should be obtained when ictal features are noted among patients presenting with headache.